PELAKSANAAN MODEL KEWIRAUSAHAAN DALAM DUNIA PENDIDIKAN - Hasnawati, Hasnawati; Wahira, Wahira; Sahabuddin, Romansyah; Khaerani, Khaerani (Universitas Negeri Makassar, 2024)
The implementation of the entrepreneurship model in education today is something that needs to be considered optimally. Therefore, an understanding is needed related to the implementation of the entrepreneurship model in the world of education. Some entrepreneurship models in education include integrated models in learning, learning through extracurricular activities, habituation of culture and values in all activities and school atmosphere, and Entrepreneurship Subject models. Thus, the implementation of the entrepreneurship model does not always have to be fixated on one model, but can be combined from several entrepreneurship models, which can be named an integrated entrepreneurship model. With this model, entrepreneurs in the world of education must be able to implement it optimally so that the implementation process can run more effectively and efficiently.